The association of early infections and atopic dermatitis. A retrospective case-control study in Chinese children in primary care in Hong Kong. - Lee, A.; Chuh, A.; Wong, W. (European Journal of Pediatric Dermatology, 2006)
The increasing prevalence of atopic dermatitis (AD) in developed countries has been postulated to be related to better hygiene leading to lack of exposure of infants to infections. The objective of this study is to investigate the association of early infections with AD in Chinese children in Hong Kong. Our setting were two primary care surgeries run by a family physician with training and qualifications in pediatrics and in dermatology. Most children were under our continuous care since early infancy. We searched our database and retrieved 132 medical records of infants and children (below eight) with AD fulfilling the United Kingdom Working Party diagnostic criteria of AD seen by us in 12 months. Children with a label of AD but not fulfilling the diagnostic criteria were excluded. Children who were not continuously cared by us since they were born were also excluded. For each child with AD, we retrieved the medical record of the next age-and-sex pair-matched child who did not have skin problems as controls. The number of children with infection before the age of six months, the number of infections, the number of hospitalizations, and the number of children having prescribed antibiotics before six months were insignificantly different in the study and control subjects. We conclude that there is no significant association between early infections and the risk of AD for Chinese children in Hong Kong.